How could science–policy interfaces boost food system transformation? - Hainzelin, Etienne; Caron, Patrick; Place, Frank; Alpha, Arlene; Dury, Sandrine; Echeverria, Ruben; Harding, Amanda (Springer, 2023)
The world’s food systems must be transformed to make healthier diets more accessible for all, while increasing the sustainability and resilience of these systems, as clearly called for in the 2030 Agenda for Sustainable Development. Scientists and policymakers are among the actors necessary for this transformation. This chapter reviews the importance of the interfaces between science and policy and how these interfaces can become more active and effective. There is no single science—policy interface, but rather many, at different scales, for different functions, addressing different challenges. Strengthening, connecting, and streamlining these interfaces can ensure the consistency and success of food system transformation. To improve science—policy interfaces, the scientific community should (1) generate actionable knowledge, data, and metrics to move beyond obstacles, and address trade-offs and barriers to change, including power asymmetry, path dependency, conflicts of interest, and risk and uncertainty; (2) articulate models, knowledge, and place-based innovations for designing, implementing, and assessing specific transformative pathways—this requires specific arrangements, dialogues, and approaches, including scientific ones; (3) connect expertise mechanisms, such as scientific committees, to address multisectoral and multiscale processes for sustainable development; and (4) strengthen scientific cooperation through major challenge-oriented alliances and programs. Science—policy interfaces can play a decisive role if they are able to dovetail divergent views and overcome polarized debates and sectoral fragmentation. These interfaces must also help us to look ahead and to bridge local and global processes and actions.